Impact of Banking Performance Indicators on Share Price of Islamic Banks listed on GCC Stock Exchanges - Yasser Saleh Ali Almonifi; Vasant Bhosle (Universitas Islam Negeri (UIN) Walisongo Semarang, 2023)
AbstractPurpose - This study aims to explore the impact of banking performance indicators on share price of Islamic banks listed on GCC stock exchanges.Method - The research methods related to quantitative approach are based on the data collected through the reports of 17 Islamic banks and 7 stock exchanges in GCC for the period from 2012 to 2021, where the panels approach tests and fixed effect model were used to measure performance.Result - The study findings indicate that return on assets has a negative and non-significant impact on the Islamic banks share price in the stock exchanges, also, the return on equity and price/earnings ratio have a non-significant positive impact on the banks share price, while there is a negative and significant impact between earnings per Share and the banks share price index.Implication - This research has significant administrative and applied implications. To gain a competitive advantage and achieving a greater market value, banks can further improve their investment performance. Furthermore, this research highlights the importance of developing Islamic banking performance and enhancing investment and financing strategies for stakeholders in Islamic banks, as well as in the financing and investment sector.Originality - This study is considered as one of the main studies contributing to the analysis of the impact of banking performance indicators on share price of Islamic banks listed on GCC stock exchanges.